System Performance Comparison Between Crystalline and Thin-Film Technologies under Different Installation Conditions - Gan, Chin Kim; Tan, Pi Hua; Khalid, Shamsudin (2013)
This paper presents a comparison between the performance of crystalline and thin-film type photovoltaic (PV) module technologies. The rooftop and ground mounted PV system installation conditions were considered in the study. The respective system performances were compared in terms of total energy generated, energy yield and Levelized Cost of Energy (LCOE). The PV system installation site’s meteorological parameters were obtained from Meteonorm, a comprehensive meteorological database for solar applications and system design. The key findings suggest that the ground mounted thin-film system has the highest energy yield, which is mainly driven by its lower temperature coefficient and greater airflow. However, under the current Feed-in Tariff scheme in Malaysia, the rooftop thin-film PV system installation has the highest economic benefit for the utility scale PV power plant.